Enhancing Eighth-Grade Students’ Plane Geometry Problem-Solving Skills through Realistic Mathematics Education : A Case Study at São José Operário Balide, Timor-Leste - Zelio da Conceicao Freitas; João Helio da Costa Alves; Meliana Yanti Mali (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the influence of the Realistic Mathematics Education (RME) approach on eighth-grade students’ ability to solve plane geometry problems at Ensino Básico 3° Ciclo São José Operário Balide during the 2025 academic year. The research followed a quantitative pre-experimental design using a one-group pre-test and post-test structure. Prior to data collection, a try-out test consisting of 15 items was administered to 10 non-sample students to determine the validity and reliability of the research instrument. The results indicated that 10 items met the validity criteria, while 5 items were invalid. All 10 valid items demonstrated acceptable reliability, allowing their use as the main instrument for measuring students’ problem-solving ability. After administering the pre-test and post-test to the sample class, normality testing using the Lilliefors method showed that both pre-test (Lmax = 0.3707 > Ltabel = 0.14) and post-test data (Lmax = 0.4562 > Ltabel = 0.14) were normally distributed. Linearity testing further revealed that Fcount < Ftable (−28.18 < 2.78), indicating a linear relationship between the two sets of scores. Given the conditions of normality and linearity, the paired-sample t-test was conducted to determine the effect of the RME approach. The results showed a significant difference between the pre-test and post-test mean scores, demonstrating that RME positively influenced students’ geometry problem-solving abilities. These findings support the view that RME, grounded in constructivist principles, effectively encourages active student participation and enhances conceptual understanding in mathematics learning.